(untitled) (Eureka Journal of Civil, Architecture and Urban Studies, 2026)
Iraq is faced with extreme seasonal temperatures and rapidly growing traffic, so it will be a priority to ensure that the country has resilient road infrastructure. In many cases, traditional asphalt is unable to hold up in such conditions over time and will start to wear out before it should. The result is a demand to upgrade pavement design using innovative enhancement materials, in order to extend the life of pavements and reduce the frequency and cost of maintenance works in hot arid regions. Finally, there are problems with road maintenance systems and periodic monitoring, as there is no reliable, fixed database to assess the surface layer efficiency of various roads periodically. The purpose of the study specifically addresses the asphalt surface layer, given its direct importance in all these problems. Regular bitumen is relatively weak, and the goal is to improve the properties of the asphalt surface mixture through some additives to the bitumen to enhance its properties. The research methodology involves designing an asphalt mixture using RMP and conducting the required laboratory tests. The base bitumen was modified by adding 4.2% SBS polymer in accordance with AASHTO M320 specifications and achieving a PG76-10 performance grade. The results demonstrated improved stress resistance and enhanced Marshall stability, along with reduced permanent deformation and increased resistance to high temperatures. It is recommended to adopt this mixture according to the stated proportions, considering the direct variables, each according to the specific requirements of the project conditions.